Estudo de compatibilidade e estabilidade térmica do ácido retinóico, hidroquinona e excipientes por análise térmica - Mendonça, Cândida Maria Soares de (2014)
Retinoic acid (RA) and hydroquinone (HQ) assets are widely used in pharmaceutical and cosmetic formulations, for having depigmenting properties and are largely produced in drugstores. To assist in the development of formulations containing the active RA and HQ National Forms of Brazilian Pharmacopoeia (2005 and 2012 ) proposes formulations with different excipients such as cetyl alcohol (AC), cetostearyl alcohol (ACT), methylparaben (MTP), propyl paraben ( PPB), glycerin (GLY), dipropylene glycol (DPG), imidazolidinil urea ( IMD ), cyclomethicone (CCM ), butylated hydroxytoluene (BHT), octyl stearate (ETO), EDTA, decil oleate (ODC) and hydroxipropymethyl celullose (HPMC). One of the difficulties found in most cosmetic formulations is the large number of incompatibilities between the components of the formulations, so the aim this study was to evaluate thermal stability and interactions between these active pharmaceutical ingredients and excipients. The depigmenting agents were analyzed by DSC and TG and excipients were analyzed by TG. The dynamic thermogravimetric curves were obtained on a SHIMADZU thermobalance, model DTG-60, using an alumina crucible, at the heating rate of 10ºC min-1, in the temperature range of 25-900 ºC, under an atmosphere of nitrogen at 50 mL min-1. The DSC curves were obtained using Shimadzu calorimeter, model DSC-60, using aluminum crucible, at the heating rate of 10ºC min-1, in the temperature range of 25-400ºC. The thermogravimetric and calorimetric curves were analyzed using TASYS software SHIMADZU. In this study no were found interactions between AR and the following excipients: MTP, PPB, IMD, ODC, EDTA, CCM, ETO, HPMC. However, were found interactions with the following excipients: AC, ACT, BHT, GLI and DPG. For HQ were found interactions with IMD and DPG. Interactions remained even changing proportions of the mixtures and the ternary. Thus, the studies conducted with excipients of National Formulary from 2005 and 2012 showed that these new excipients do not interact by thermogravimetry with the active pharmaceutical ingredients of this study